2022
DOI: 10.1002/ajcp.12608
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and depressive symptoms of youth: Examining prospective and interactive associations with mentoring relationship quality

Abstract: A significant body of research has demonstrated that mentoring relationships support positive youth development. The quality of the mentoring relationship has been identified as a predictor of positive youth outcomes. However, limited research has examined how engagement in a mentoring program may be related to youth depressive symptoms specifically. The current study utilized a sample of 2003 youth participating in mentoring programs across the country (Mage = 12.32, SD = 1.42, 55.1% female) from diverse raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Notably, there was a significant interaction between these two factors, such that the strongest outcomes were found in matches characterized by strong youth‐rated relationship quality and mentor‐reported use of instrumental activities. In a combined sample of several mentoring programs across the United States, Browne et al (2022) recently found that youths' positive ratings of mentor supportiveness were associated with greater reductions in depressive symptoms over the course of the program, although mentor‐reported relational closeness was not associated with symptom change.…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, there was a significant interaction between these two factors, such that the strongest outcomes were found in matches characterized by strong youth‐rated relationship quality and mentor‐reported use of instrumental activities. In a combined sample of several mentoring programs across the United States, Browne et al (2022) recently found that youths' positive ratings of mentor supportiveness were associated with greater reductions in depressive symptoms over the course of the program, although mentor‐reported relational closeness was not associated with symptom change.…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
“…Using a large archival database with 6468 youth mentoring relationships across 170 distinct programs in the United States, Kupersmidt and colleagues (2017) identified a range of youth characteristics associated with premature termination, including anxiety and depressive symptoms, academic difficulties, teenage pregnancy, substance use, anger management problems, and ADHD diagnosis. In a recent contribution, Browne et al (2022) found that youth's level of depression at baseline predicted poorer youth‐reported (but not mentor‐reported) relationship quality, in a sample that included 23 school‐ or community‐ based programs across the United States. On the other hand, Weiler et al (2019) did not find the severity of youth's behavioral, academic, or mental health problems to be significantly associated with relationship outcomes.…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
See 1 more Smart Citation